Long-Circulating Thermosensitive Liposomes for the Targeted Drug Delivery of Oxaliplatin - Li Y (Dove Medical Press, 2020)
Yanan Li,1 Pengcheng Xu,1 Dongsheng He,1 Bohui Xu,2 Jiasheng Tu,1 Yan Shen1 1China Pharmaceutical University, Center for Research Development and Evaluation of Pharmaceutical Excipients and Generic Drugs, Nanjing 210009, People’s Republic of China; 2School of Pharmacy, Nantong University, Nantong 226001, People’s Republic of ChinaCorrespondence: Yan Shen Tel/Fax +86-25-83271305Email shenyan@cpu.edu.cnIntroduction: Oxaliplatin (L-OHP) is a well-known third-generation platinum anticancer drug with severe systemic- and neuro-toxicity. The main objective of the current research was to develop a targeted long-circulating thermosensitive smart-release liposome (LCTL) system for better therapeutic efficacy and less toxicity.Methods: The reverse-phase evaporation method (REV) was used to prepare L-OHP loaded LCTL (L-OHP/LCTL). The physical characteristics were evaluated including encapsulation efficiency (EE), size, zeta potential and stability. The release behavior, cytotoxicity and in vivo evaluation were also carried out.Results: EE of LCTL was around 25% with a uniform size distribution, and LCTL achieved almost complete release at 42°C while it was only 10% at 37°C. Moreover, the LCTL showed significantly higher cytotoxicity at 42°C than that at 37°C. The in vivo results indicated LCTL could target tumors and enhance retention for more than 24 h, thereby enhancing anti-tumor efficacy on 4T1-bearing mice.Discussion: These results indicated that LCTL not only possessed a prolonged circulation time but it also enhanced accumulation and achieved selective release at the tumor sites. Conclusively, LCTL could serve as a promising carrier for oxaliplatin delivery to treat solid tumors.Keywords: delivery, oxaliplatin, thermosensitive, pharmacokinetic properties, tumor targeting